2012
DOI: 10.1021/jp3007624
|View full text |Cite
|
Sign up to set email alerts
|

Site Energies of Active and Inactive Pheophytins in the Reaction Center of Photosystem II from Chlamydomonas reinhardtii

Abstract: It is widely accepted that the primary electron acceptor in various Photosystem II (PSII) reaction center (RC) preparations is pheophytin a (Pheo a) within the D1 protein (Pheo(D1)), while Pheo(D2) (within the D2 protein) is photochemically inactive. The Pheo site energies, however, have remained elusive, due to inherent spectral congestion. While most researchers over the past two decades placed the Q(y)-states of Pheo(D1) and Pheo(D2) bands near 678-684 and 668-672 nm, respectively, recent modeling [Raszewsk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(54 citation statements)
references
References 79 publications
5
49
0
Order By: Relevance
“…We proposed recently (Acharya et al 2012a) that the NPHB process in isolated RCs of PSII can also take place Photosynth Res during the stage when the continuous wave laser is on, and the primary electron donor is in the long-lived 3 Chl D1 triplet (Renger and Schlodder 2010), although due to a broad distribution of CT rates the slower charge separation kinetics may also contribute to persistent hole formation (Riley et al 2004). Thus it is feasible that the persistent nonphotochemical holes burned in isolated RCs could correspond to a bleach of the briefly decoupled Pheo D1 (during the long-lived triplet and/or charge-separated states if Q A is present), which could explain why the shallow persistent holes burned in isolated PSII RCs (within the zero-phonon hole action spectrum) revealed an excited state lifetime close to the Pheo radiative lifetime of a few ns (Zazubovich et al 2003) even though charge separation occurs on a ps time scale (Acharya et al 2012b;Chauvet et al 2015;Kwa et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We proposed recently (Acharya et al 2012a) that the NPHB process in isolated RCs of PSII can also take place Photosynth Res during the stage when the continuous wave laser is on, and the primary electron donor is in the long-lived 3 Chl D1 triplet (Renger and Schlodder 2010), although due to a broad distribution of CT rates the slower charge separation kinetics may also contribute to persistent hole formation (Riley et al 2004). Thus it is feasible that the persistent nonphotochemical holes burned in isolated RCs could correspond to a bleach of the briefly decoupled Pheo D1 (during the long-lived triplet and/or charge-separated states if Q A is present), which could explain why the shallow persistent holes burned in isolated PSII RCs (within the zero-phonon hole action spectrum) revealed an excited state lifetime close to the Pheo radiative lifetime of a few ns (Zazubovich et al 2003) even though charge separation occurs on a ps time scale (Acharya et al 2012b;Chauvet et al 2015;Kwa et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…3 in Supporting Information), we predict that the origin band of the Pheo D1 emission (in PSII-cc and PSII-m) should be much narrower (as observed) than the corresponding emission band observed in isolated RCs. This is because in isolated RCs, in the absence of the long wavelength CT state(s) and in most cases with Q A lost, the charges may also recombine to the excited state of the Chl exciton leading to additional emission and resulting in broadening of the total fluorescence band (Acharya et al 2012a, b). In fact, it has been shown that emission (4-77 K) of isolated PSII RC from spinach has signature modes of both Chl and Pheo, although the Pheo contribution is at most 10 % (Konermann et al 1997;Kwa et al 1994;Peterman et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we propose an alternative mechanism based on pseudo-rephasing and pseudo-free-induction-decay (FID) in a binary system and understand the negative peak shift as the result of macroscopic interference 1,16 . We evaluate the effect of the electronic energy gap and electronic coupling constants asymmetry between the two components of the binary system [17][18][19][20][21] . A specific example of such a system is the photosynthetic reaction center, which in all known cases posses an approximate C 2 symmetry.…”
Section: Introductionmentioning
confidence: 99%